Penyuluhan Kenakalan Remaja Di Smpn 2 Asembagus - Shofa Zahrotul Muna; M. Syakur (Jurnal Ilmu Bimbingan dan Konseling, 2026)
Juvenile delinquency is an increasingly prevalent issue at the junior high school level, including in Asembagus District. Various forms of deviant behavior such as bullying, free dating, brawls, truancy, gadget addiction, and peer pressure pose serious challenges to students’ psychological and social development. This community service activity aims to enhance students’ awareness and understanding of the dangers of juvenile delinquency, as well as to strengthen the role of schools and guidance and counseling teachers in prevention efforts.This program was implemented among ninth-grade students in junior high schools throughout Asembagus District, involving a total of 457 participants. The methods used included interactive lectures, group discussions, educational games, role-playing, and small group counseling. Evaluation was conducted through observation and interviews to assess students’ responses and level of understanding. The results of the activity showed that students were highly enthusiastic and actively participated in all sessions. The counseling sessions were conducted in a conducive atmosphere, with students demonstrating a strong interest during the question-and-answer sessions. Psychologically, there was an increase in students’ self-awareness regarding the risks of juvenile delinquency. Behaviorally, initial positive changes were observed, such as increased confidence in asking questions, improved ability to identify risky behaviors, and a willingness to avoid negative influences.For schools and guidance and counseling teachers, this activity provided valuable insights into students’ conditions and strengthened strategies for character development. Overall, this counseling program is considered effective in raising students’ awareness and providing a solid foundation for the ongoing prevention of juvenile delinquency within the school environment.